Hungary: Doomed to Victory - Kecső, Gábor (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter focuses on the Hungarian state aid law and policy and its recent challenges. It also covers the historical view, economic aspects, and basic statistics while providing an overview of the domestic applicable law, fully considering the fact that the other chapters are devoted to the EU law on state aid policy and taxation matters. State aid may produce contradictory effects. On the one hand, it can restore market efficiency, while on the other, it can adversely intervene in the market mechanisms. Furthermore, political goals can be channelled through governmental subsidies. Without geographical and sectoral analyses of the economy, the question of the state aid’s raison d’être cannot be answered. In Hungary, domestic state aid law is merged with the EU law; hence, a sovereign state aid policy cannot be pursued. This process started even before the country’s accession to the EU. Aid measures under the general block exemption comprised the largest part of the spending between 2011 and 2021. Notified aid was the other important element in this period. In the last couple of years, the ratio changed; notified aid overtook general block exemption in terms of estimated value. Many large investments were financed through state aid between 2014 and 2022 in Hungary. Hungarian state aid institutions have thus proven their practical efficiency. The country was successful in addressing the impact of COVID-19 and the Russo-Ukrainian War through the provision of state aid. National tax sovereignty was not subordinated to the state aid law of the EU in the judgements related to Hungary in the CJEU. Some room for manoeuvre is preserved in its tax policy, especially in applying progressive tax rates on turnover, even if the multinational companies bear a higher burden of taxes than their domestic competitors. When the crises blow over, Hungary is keen on maintaining effective prohibition of state aid in the EU and making the most successful use of exceptions to the main rule. The country’s near future is determined by how it will use the Recovery and Resilience Facility. Keywords: state aid in Hungary, the Hungarian regional aid map, treatment of the COVID-19 era with state aid, state aid under the Russo-Ukrainian war period